Assessment of Activity Concentrations and Their Associated Radiological Health Risks in Commercial Infant Formulas in Thailand - Worawat Poltabtim (Science Faculty of Chiang Mai University, 2019)
This work assessed the activity concentrations of 226Ra, 232Th, 40K, and 137Cs, their corresponding annual effective doses, and their radiological health risks associated with the consumption of infant formulas in Thailand. The results showed that the average (± standard deviation) activity concentrations of 226Ra, 232Th, 40K, and 137Cs radionuclides were 3.20±0.51 Bq kg-1, 1.24±0.10 Bq kg-1, 213.20±25.50 Bq kg-1, and 4.90±0.74 Bq kg-1, respectively, leading to an average annual effective dose for infants aged ≤1 year and 1–2 years of 762.82±91.34 µSv year-1 and 189.60±22.47 µSv year-1, respectively, and radiological health risks of (5.63±0.66)×10-6 and (3.77±0.44)×10-6, respectively. The overall results suggested that infant formulas in Thailand posed no significant effective dose and radiological health risks, implying safe consumption for infants.